Efectos sorpresivos de la cláusula de la nación más favorecida (CNMF) en materia de inversiones extranjeras (2009)
Nowadays, the Most Favored Nation (MFN) clause, which was incorporatedalmost automatically in Bilateral Investment Treaties (BIT) during the decadesof 1960 and 1970, reveals a surprising dynamic. By means of different awards of the International Center for Settlement of Investment Disputes (ICSID) our article presents the “evolution” or change of conception that this clausehas undergone. For this purpose it is necessary to analyze the clause mechanism, which a priori limited to importation of substantial provisions, seems to be implicitly authorized to insert procedural provisions too. The“new” feature of the MFN clause imposes a retrospective study of itsprinciples, its wording and its aim. Such feature is not the consequence of modifications to the wording of the clause itself, but rather is the result of the assessments made by arbitrators, States and investors. That is why, the useof the MFN clause besides allowing a higher degree of liberalization in theinvestment sector, affects other structures of international law and highlightsthe role of States, investors and ICSID in the reinterpretation of MFN clause.